The Conflicting Conventions of Care: Transformative Service as Justice and Agape. (February 2022) - Varman, Rohit; Vijay, Devi; Skålén, Per
In this study, we examine the conflicts and unintended consequences that arise from the diverse social conventions constituting a transformative service. We draw on convention theory and an ethnographic study to interpret a community-based palliative care initiative in Kerala (India) as a transformative service system. We contribute to transformative service research by developing a dialectical transformative service system framework that is a synthesis of the calculative conflict-ridden regime of justice and the noncalculative regime of agape based on love. In this framework, the calculative regime of justice has civic conventions at its core and industrial, inspired, market, domestic, and fame conventions as ancillaries. While the regime of justice is associated with the undesired, unintended consequence of conflicts, the regime of agape constitutes a desirable unintended consequence. Our framework provides a microlevel understanding of disputes and their reconciliation, advances a diffused understanding of worth that ruptures the binary of legitimate or illegitimate actions, and delineates the significance of morality. Our study also contributes by explaining agape's role in transformative service, particularly in health and caregiving.